MUSISI MUDA, REFLEKSIVITAS DIRI DAN KARIER DIY DI ERA MODERNITAS LANJUT - Oki Rahadianto Sutopo (Jurnal Analisa Sosiologi, 2022)
This article examines the practice of self-reflexivity among young Indonesian musicians in the era of late modernity. In particular, young musicians’ musical practice from amateur phase into Do It Yourself (DIY) career become an important temporal and spatial dimensions of the analysis. This article applies self-reflexivity theory from Anthony Giddens as a tool of analysis. In addition, I also synthesis Giddens’ theory with youth culture and youth transition perspectives. This article makes use of qualitative method specifically life biographies as a tool to capture wider narrative of young musicians throughout their life course. This research finds that young Indonesian musicians are able to reflexively adaptive during transition from amateur into DIY carrier. Narratives of young musicians also reveal the empowering effect during their process of formulation and re-formulation of reflexive self. Young musicians are able to achieve self-actualization based on their individual’s aspiration. Thus, the self-reflexive characteristic as shown by young Indonesian musicians in this article can be a positive example for young people to maintain their transition in the era of late modernity. Keywords: Young Musicians, Self-Reflexivity, Youth Culture, DIY Career AbstrakArtikel ini membahas mengenai refleksivitas diri musisi muda Indonesia dalam era modernitas lanjut. Secara spesifik, praktik bermusik dalam perjalanan dari fase amatir menjadi karier Do It Yourself (DIY) menjadi dimensi temporal dan spasial yang penting. Teori refleksivitas diri dari Anthony Giddens digunakan sebagai alat bantu dalam melakukan analisis. Selain itu, teori tersebut juga disintesiskan dengan perspektif budaya kaum muda dan transisi. Secara metodologis, artikel ini menggunakan metode kualitatif dengan pendekatan life biographies untuk melihat narasi yang lebih luas dalam daur hidup kaum muda. Berdasarkan temuan penelitian ditunjukkan bahwa musisi muda secara refleksif mampu adaptif baik pada fase amatir maupun pada fase karier DIY. Disisi lain, narasi musisi muda menunjukkan bahwa pembentukan dan penataan ulang diri secara refleksif justru bersifat memberdayakan dikarenakan baik dalam fase amatir maupun karier DIY mereka mampu melakukan aktualisasi diri sebagaimana yang diinginkannya. Karakteristik refleksivitas diri dari musisi muda dalam artikel ini dapat menjadi contoh positif dalam menjalani transisi kepemudaan di era modernitas lanjut.Kata Kunci: Musisi Muda, Refleksivitas Diri, Budaya Kaum Muda, Karier DIY